Reflections on Local and Economy-wide Effects of Territorial Competition - Poot, Jacques (School of Management Working Papers, 1999)
As part of the global trend towards greater reliance on market forces in public sector activities, there is a growing tendency in many countries to devolve the responsibility for regional development to regional and local authorities. From this perspective, vigorous competition between such authorities to attract productive enterprises, finance and households is expected to enhance the competitiveness of regions and to lead to higher local and national growth. Yet uncoordinated policies that do not take network and external spillover effects into account may be wasteful in the short run and lead to lower growth in the long run. This paper focuses on lessons from conventional and new theories of growth for understanding the impact of territorial competition. In addition, notions of regional competitiveness and their effectiveness as indicators of the regional growth potential are discussed. Although increasing competitiveness may induce higher growth, observed high growth rates are sometimes erroneously interpreted as evidence of competitiveness. Forces leading to convergence and divergence in an open regional system are identified and the impact of territorial competition is addressed. Specific attention is paid to regional incentives to encourage inward investment. While footloose firms appear responsive to such incentives, regional competition in the form of tax or non-tax incentives may bear little relationship with the spatial variation in unemployment rates or other indicators of regional economic problems. Incentives are therefore not always welfare enhancing. Some issues for further research are suggested.